2012
DOI: 10.1016/j.jclinepi.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative complexity: a functional, patient-centered model of patient complexity can improve research and practice

Abstract: With its components largely supported by existing literature, the model has implications for analytic design, clinical epidemiology, and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
654
2
24

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 540 publications
(691 citation statements)
references
References 154 publications
11
654
2
24
Order By: Relevance
“…This activity requires 'work' on behalf of the patient, and levels of literacy and numeracy influence patients' self-assessments of their needs and capacity to respond appropriately to this growing workload. (Shippee et al, 2012) As we have noted, previous research has shown that literacy skills are important; our research goes further, indicating that numeracy is equally and independently important, and different from literacy. Service delivery needs to recognise this distinctiveness and measures to address shortfalls in literacy and numeracy need to be aware of their implications for self-assessments of health.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This activity requires 'work' on behalf of the patient, and levels of literacy and numeracy influence patients' self-assessments of their needs and capacity to respond appropriately to this growing workload. (Shippee et al, 2012) As we have noted, previous research has shown that literacy skills are important; our research goes further, indicating that numeracy is equally and independently important, and different from literacy. Service delivery needs to recognise this distinctiveness and measures to address shortfalls in literacy and numeracy need to be aware of their implications for self-assessments of health.…”
Section: Discussionsupporting
confidence: 65%
“…We view health status both as a likely consequence of shortcomings in health service uptake and also as a construct deeply structured in its own right by social inequality at both the individual and area level. Within this context, following the cumulative complexity model of Shippee et al (2012), we see health status as relating to the burden of disease, and literacy and numeracy as elements of patient capacity to deal with that burden and the associated treatment regimes.…”
Section: Study Aimsmentioning
confidence: 99%
“…27 This includes understanding the potential negative impact of developing a clinical plan which, in order to operationalize, requires resources in excess of the patient's capacity at that time. 27 Minimally disruptive medicine, a promising theoretical approach for improving the care of complex clients, embodies the awareness of capacity in achieving patient-centered care while "imposing the smallest possible treatment burden on patients' lives." 28 This study, although not without its limitations, provides an in-depth exploration of the experiences of a small number of patients living with HIV, recruited from a single facility in Toronto, Canada after relatively long hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14]16,17 Holzhausen and colleagues developed a conceptual framework, standardized instruments, and indicators for continuous monitoring of multimorbidity and associated healthcare needs in the population 65 years and older for a longitudinal epidemiological study. 15 Their model includes concepts of multimorbidity and its consequences, quality of life, healthcare services utilization, personal and social resources that modify the association between multimorbidity and outcomes measures, and sociodemographic variables.…”
Section: Purpose and Application Of Existing Modelsmentioning
confidence: 99%
“…13 Safford's Vector Model of Complexity was developed to inform clinical management of complex patients. 10,16 This model defines patient complexity at a given time-point along socioeconomic, cultural, biological/genetic, environmental/ ecological and behavioral axes that interact as health determinants; multimorbidity is one aspect. 10 In this model, patients can have greater vulnerability in one or more axes and axes contributing to complexity can change over time to reflect complexity's dynamic nature.…”
Section: Purpose and Application Of Existing Modelsmentioning
confidence: 99%